1997
DOI: 10.1088/0741-3335/39/2/001
|View full text |Cite
|
Sign up to set email alerts
|

Negative magnetic shear modes of operation in the Alcator C-Mod tokamak near the beta limit

Abstract: The stability properties of non-inductively driven, reversed shear type current profiles that may be achieved for Alcator C-Mod tokamak-like parameters (aspect ratio R/a=3) are examined. It is found that without a conducting wall, the best stability results (ON up to 3.7) are achieved for highly triangular plasmas (b = 0.7) at qmin=2.2, for relatively broad pressure profiles (p(0)/pavg = 2.8) and large values of rmin/a(= 0.75). For elliptical or circular cross-section plasmas with little triangularity, the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…9, using the TRANSP code with LSC [17], predicts 30-40 kA of LHCD, localized off axis with a peak at r/a=0.65. Extrapolation to the planned upgrade power of 2.7 MW predicts ~150 kA in comparable discharges, in line with advanced scenario modeling [18]. Further reduction of density would clearly be desirable.…”
Section: To 14 S (A) Notable Changes Include a Decrease In Electronsupporting
confidence: 57%
See 1 more Smart Citation
“…9, using the TRANSP code with LSC [17], predicts 30-40 kA of LHCD, localized off axis with a peak at r/a=0.65. Extrapolation to the planned upgrade power of 2.7 MW predicts ~150 kA in comparable discharges, in line with advanced scenario modeling [18]. Further reduction of density would clearly be desirable.…”
Section: To 14 S (A) Notable Changes Include a Decrease In Electronsupporting
confidence: 57%
“…Simulation of these discharges continues in an effort to understand the evolution more clearly. In other related experiments [18] delay of q 0 = 1 onset has been demonstrated at I p = 0.8 MA (q 95 =4.2), in the range required for hybrid scenario experiments that will help assess the properties of this regime on ITER. Lower hybrid heating and current drive experiments on the Alcator C-Mod tokamak have been extended to detailed measurements of the driven current and comparisons to models as well as application of LHCD to plasma scenarios that will lead to eventual advance tokamak conditions for several current relaxation times.…”
Section: Use Of Lhcd During the Current Rampmentioning
confidence: 84%
“…A number of authors have calculated that the stability limit can be increased by a broadening of the pressure profile (Turnbull 1996(Turnbull , 1997Phillips 1996;Bonoli 1997;Manickam 1994). The impact of the pressure profile on the ideal stability limit for a specific q profile and for a D-shape equilibria (K = 1.8, 6 = 1.7) is shown in Fig.…”
Section: Ts Taylormentioning
confidence: 99%
“…Although previous experimental [12][13][14][15][16][17] and theoretical 7,9,13,18,19 work has shown that ␤ limits increase with pressure profile width, much of the focus has been on equilibria with internal transport barriers and characteristically high pressure peaking. In this previous work, the dependence of ␤ limits on q min , 10,11,14 and the potential for high f BS at high q min ͑Ref.…”
Section: Introductionmentioning
confidence: 99%